Atlas of hematology - Saxena, Renu (Jaypee Brothers Medical, 2012)
Atlas of Hematology discusses a range of haematological disorders and their management. The criteria for diagnosis are listed in tables for ease of use, along with peripheral smear and bone marrow examples, and biopsy samples illustrating normal and abnormal results for both haematological and non-haematological diseases. Topics covered include Anaemias, Bone Marrow Failure Syndromes, Platelet Disorders, Leukemia, Myelofibrosis and Stem Cell Transplant. Well-illustrated clinical photographs and microphotographs of some more common disorders are included